(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2021)
Today we are witnessing the rapid development of the laser industry. Laser sources with new wavelengths, higher powers and energies, different modes of operation (generation of laser pulses), as well as various applications in industry, medicine, environmental protection etc. are emerging. This requires the development of new physical methods and principles for accurate measurement of power, energy, and other parameters of laser sources. In different types of laser technological processes, accurate measurement of laser power is extremely important in terms of quality, repeatability, and validation of the process. In most cases, accurate laser power measurement is a difficult task, especially when working with high-power lasers or having to perform real-time measurements.The report analyses and systematizes the physical principles and methods on which existing laser measuring instruments are based. This research also aims to help researchers and technologists find and develop new approaches to solving this challenging measurement problem.